Compression-extension transition of continental crust in a subduction zone: A parametric numerical modeling study with implications on Mesozoic-Cenozoic tectonic evolution of the Cathaysia Block - Zuo, Xuran; Chan, Lung Sang; Gao, Jian-Feng (PLOS ONE, 2017)
The Cathaysia Block is located in southeastern part of South China, which situates in the west Pacific subduction zone. It is thought to have undergone a compression-extension transition of the continental crust during Mesozoic-Cenozoic during the subduction of Pacific Plate beneath Eurasia-Pacific Plate, resulting in extensive magmatism, extensional basins and reactivation of fault systems. Although some mechanisms such as the trench roll-back have been generally proposed for the compression-extension transition, the timing and progress of the transition under a convergence setting remain ambiguous due to lack of suitable geological records and overprinting by later tectonic events. In this study, a numerical thermo-dynamical program was employed to evaluate how variable slab angles, thermal gradients of the lithospheres and convergence velocities would give rise to the change of crustal stress in a convergent subduction zone. Model results show that higher slab dip angle, lower convergence velocity and higher lithospheric thermal gradient facilitate the subduction process. The modeling results reveal the continental crust stress is dominated by horizontal compression during the early stage of the subduction, which could revert to a horizontal extension in the back-arc region, combing with the roll-back of the subducting slab and development of mantle upwelling. The parameters facilitating the subduction process also favor the compression-extension transition in the upper plate of the subduction zone. Such results corroborate the geology of the Cathaysia Block: the initiation of the extensional regime in the Cathaysia Block occurring was probably triggered by roll-back of the slowly subducting slab.